Teaching research ethics as active learning: reading Venkatesh and Goffman as curriculum resources. Issue 3 (4th May 2017) - Tolich, Martin; Choe, Louisa; Doesburg, Adam; Foster, Amy; Shaw, Rachel; Wither, David
Abstract: The pedagogy of teaching research methods, let alone research ethics, is an under-researched field. In this article a sociology lecturer connects five postgraduate students in a qualitative research ethics course with two novice ethnographers' candid empirical studies. While it is common for students to read articles and books on the topic, what was unusual in this ethics course was assigning the readings without priming the students of the ethical concepts of autonomy, do no harm, respect for persons or beneficence. The article documents how these students drew on their prior tacit knowledge of ethics to critique these two empirical studies both in classroom discussions and later in their written assignments. Each student wrote an account of the two texts before joining forces to construct a joint auto ethnographic account based on their reflective journals and on transcriptions of their classroom discussions. Invariably the students' tacit knowledge allowed them to successfully locate core ethical issues within these two texts.